Penambahan Madu Bunga Kopi (Coffea sp.) terhadap Kualitas Kefir Ditinjau dari Karakteristik Mikrobiologi - Astri Wulandari; Purwadi Purwadi; Firman Jaya (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2017)
The Objective of this research was to determine the best concentration of addition coffee flower honey to kefir based on total plate count, lactic acid bacteria, acidity, and pH value. The materials used in this research were honey kefir made from cow’s milk, kefir grains, and coffee flowers honey. The method used in this research was experimental with Completely Randomized Design by 4 treatments and 4 replications and continued by using Duncan’s Multiple Range Test. The result showed that the effect of addition coffee flowers honey was not significantly different (P>0.05) on total plate count, lactic acid bacteria, acidity, give highly significant different (P<0.01) on pH value. Addition 20% of  coffee flower honey was the best treatment with quality of total plate count 6.21 ± 0.60 log CFU/mL, total lactic acid bacteria 6.16 ± 0.14 log CFU/mL, acidity 0.76 ± 0.11 % and pH value 3.596 ± 0.021. Further study is needed to figure the storability of honey kefir.